Pane e Cioccolata: The impact of native attitudes on return migration - Augustin de Coulon; Dragos Radu; Max Friedrich Steinhardt (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
This paper addresses the potentially causal link between native attitudes and migrants' intended duration of stay. We exploit the variation in perceived anti-immigrant sentiments using information on the media exposure of Romanian migrants in Italy. A unique shock in public attitudes towards Romanian migrants allows us to identify the impact of a change in attitudes on out-migration plans. Our results suggest a significant impact of native attitudes on settlement intentions in Italy. The subgroup analysis indicates a particularly pronounced impact for low-skilled migrants, which has important consequences for the integration prospects of migrants in Italy.
Keywords: F22; J61; 330; return migration; public attitudes; media consumption; crime